Competitive Education Marketing Management in Integrated Islamic Education Institutions: Islamic Education Interests in Modern Society - Rita Prima Bendriyanti; Suwarni Suwarni; Mukrimah Mukrimah; Silvy Sondary Gadzali; Riyanti Susiloningtyas (Al-Hayat: Journal of Islamic Education, 2022)
This study aims to produce a marketing management theory concept for competitive private Islamic educational institutions. At the same time, the locus of this research is the Integrated Islamic Junior High School (SMPIT) Khairunnas Bengkulu, Sumatra. Education is a service product produced by non-profit educational institutions so that the educational process results are visible. To learn more about education marketing, you must first know the substance and characteristics of services and marketing concepts so that the application of education marketing is in the correct position by the values and nature of education itself. This study used a qualitative approach with a case study type—data obtained from interviews, observation, and documentation. Data analysis was carried out since the researcher arrived at the research locus; after the data was collected, analysis was carried out through data compression, data presentation, and conclusion. The processes of credibility, dependability, confirmability, and transferability are used to best check the validity of the data. Research findings related to the concept of institutionally competitive marketing management are the concept of "shura expert" or guidance from a senior who is experienced in the field of education, the concept of mastering English and Arabic for students so that they can be accepted at high schools and favourite campuses even abroad, and the concept of increasing competency through extracurricular activities, especially in science and technology.